Penggunaan Istilah Asing dalam Bahasa Gaul Kaum Milenial di Media Komunikasi Virtual - Kristianti, Tri (FKIP Universitas Wisnuwardhana, 2021)
Over the years, technology has developed and revolutionized our world and daily lives. It becomes the most crucial part in our lives. The amazing tools and resources have been created, putting useful information in our fingertips. Through instant messaging apps and social media platforms, technologyâ€™s advancements have provided quicker ways to communicate. The term â€œmediaâ€ has changed the digital technology which previously refers to the necessity of news platform. Any company that helps pass information across the globe, including social media platforms like Facebook and Twitter is now called as a media company. To reinforce this circumstance, the virtual communication platforms like Instagram and TikTok become very popular among the millennial youth. They provided any contents with variety themes and current issues to catch their viewersâ€™ attention. The content creators create particular slang language which consist of acronyms or abbreviations and mostly written in English. This research is descriptive qualitative type. This research aims to analyze the use of foreign language (English) in shortening slang abbreviations among the millennials youth while communicating in virtual communication media. While phenomenology approach is used to reveal the commonality of a lived experience in using the slang language within millennials youth. The result indicated there are 70 popular words that consist of 66 abbreviations and 4 numeronyms in the slang vocabulary of the millennials used to communicate in virtual communication media; TikTok and Instagram.